Rectal Cancer International Perspectives on Multimodality Management - Czito, Brian G.; Willett, Christopher G.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2010)
This cutting-edge book delivers state of the art information on the evaluation and management of rectal cancer. Covering the spectrum of clinical management from initial evaluation and staging, to advances and controversies in management, to survivor outcomes, sphincter preservation and quality of life, it is a comprehensive resource for this rapidly changing field. Surgery, radiation therapy, chemotherapy, radiology, endoscopy, and pathology are fully explored, including the use of both novel and contemporary approaches in each of these disciplines. With examination of clinical trials in the United States and Europe, this book features the unique insights of a cadre of world renowned specialists. Rectal Cancer: International Perspectives on Multimodality Management is an engaging discussion of current and future directions. This book is necessary reading for medical, surgical, and radiation oncologists as well as pathologists, radiologists, and gastroenterologists treating primary, recurrent, and metastatic rectal cancer.
Clinical Staging: Endoscopic Techniques -- Clinical Staging: CT and MRI -- Local Excision -- Total Mesorectal Excision and Lateral Pelvic Lymph Node Dissection -- Abdominoperineal Resection, Low Anterior Resection, and Beyond -- T4 and Recurrent Rectal Cancer -- Surgical Management of Pulmonary Metastases -- Surgical and Ablative Management of Liver Metastases -- Surgical Pathology -- Chemotherapy: Concurrent Delivery with Radiation Therapy -- Chemotherapy: Adjuvant and Neoadjuvant Approaches -- Chemotherapy: Metastatic Disease -- Radiation Therapy: Adjuvant vs. Neoadjuvant Therapy -- Radiation Therapy: Short Versus Long Course -- Chemoradiation Therapy: Nonoperative Approaches -- Contact X-Ray Therapy -- High-Dose-Rate Preoperative Endorectal Brachytherapy for Patients with Rectal Cancer -- Radiation Therapy: Technical Innovations.
Keywords: Medicine; Radiotherapy; Oncology; Cancer -- Surgery; Colon (Anatomy) -- Surgery; Medicine & Public Health; Oncology; Surgical Oncology; Colorectal Surgery; Radiotherapy